ChatGPT como um recurso no processo de ensino e aprendizagem da Matemática - Moraes, Romis de Sousa (Universidade Federal do Tocantins, 2024)
In the contemporary educational scenario, the inclusion of new technological resources, such as Artificial Intelligence (AI), emerges as a promising alternative to innovate teaching and learning methods. In Brazil, the results of large-scale assessments, such as SAEB and PISA, highlight significant challenges in the educational process of Mathematics. The overall objective of this work is to propose the use of ChatGPT AI as a support resource in the teaching and learning process of Mathematics for high school teachers and students. The qualitative-quantitative research was conducted in a public school, where the effectiveness of ChatGPT in creating didactic activities and its use as a kind of tutor in student learning was observed. The analysis of the activity results indicated a significant improvement in student performance, particularly in solving problems involving counting techniques and multiplicative and additive principles. The conclusion of the study indicates that the integration of artificial intelligence tools, such as ChatGPT, can be an effective strategy to improve mathematics education. The research suggests that, with proper pedagogical guidance and ethical use, this technology can complement and enrich the educational process, offering students a more interactive and personalized learning experience.